Advanced Fluorescence Reporters in Chemistry and Biology III Applications in Sensing and Imaging - Demchenko, A. P. (Aleksandr Petrovich).; Callis, P. R.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The key element of any fluorescence sensing or imaging technology is the fluorescence reporter, which transforms the information on molecular interactions and dynamics into measurable signals of fluorescence emission. This book, written by a team of frontline researchers, demonstrates the broad field of applications of fluorescence reporters, starting from nanoscopic properties of materials, such as self-assembled thin films, polymers and ionic liquids, through biological macromolecules and further to living cell, tissue and body imaging. Basic information on obtaining and interpreting experimental data is presented and recent progress in these practically important areas is highlighted. The book is addressed to a broad interdisciplinary audience.
Interfacial behavior of fluorescent dyes. Power and weakness of nanoscopic description -- Fluorescence probing of physicochemical characteristics of the room temperature ionic liquids -- Fluorescence spectroscopy in polymer science -- Fluorescence probing in structurally anisotropic materials. From liquid crystals to macromolecules, micelles and lipid bilayers -- ptimized dyes for protein and nucleic acid detection -- Functional nucleic acids for fluorescence based biosensing applications -- Covalent labeling of biomolecules in living cells -- Tetracysteine and bipartite tags for biarsenical organic fluorophores -- Labeling of oligohistidine-tagged proteins -- In vivo imaging of vascular targets using near-infrared fluorescent probes -- Whole-body imaging of hematopoietic and cancer cells using near infrared probes.
Electronic reproduction.
Keywords: Fluorescence spectroscopy; Imaging systems in chemistry; Imaging systems in biology